Patent Ductus Arteriosus: Perinatal Risk Factors - Nizarali, Z (2012)
Background: Patent Ductus Arteriosus (PDA) is the most common heart disease among the newborn population. Besides prematurity, other factors are believed to play a significant role in this condition. Aims: Identification of perinatal risk factors associated with PDA in premature or Very Low Birth Weight Infants (VLBW). Material and methods: Transversal study including all infants admitted to a Level III Neonatal Intensive Care Unit, from January 2005 to December 2009 and included in the Very Low Birth Weight Portuguese National Database . Clinical and demographic data were analysed using a logistic regression analysis to identify risk factors for PDA. Results: A total of 318 VLBW or less than 32 weeks Gestational Age (GA) infants were enrolled, 53.6% males. Infants presenting PDA (100; 31.4%) had a lower mean BW ( 914,19 versus 1257,44 grams; p<0.001) and a lower mean GA (27.06 versus 29.77 weeks; p<0.0001). Using univariate logistic regression, both lower BW [OR: 0.99; CI (95%): 0.995-0.997] and lower GA [OR: 0.68; CI (95%): 0.61-0.75] were important risk factors for PDA. Other factors increasing the risk of PDA were: lower Apgar scores at one [OR: 0.77; CI (95%): 0.68-0.86] and five minutes [OR:0.73;CI (95%): 0.62-0.86]; need for resuscitation in the delivery room [OR: 13.1;CI(95%):3.11-55.1]; surfactant administration [OR:8.12;CI(95%):4.13-15.95]; higher CRIB score [OR:1.17;CI(95%): 1.11-1.24], and higher SNAPPEII score [OR: 1.03; CI (95%): 1.02-1.04]. The logistic multivariate regression model using all these variables identified BW [OR: 0.997; CI (95%): 0.996- 0.998] and surfactant treatment [OR: 3.99; CI (95%): 1.903-8.386] as the only risk factors contributing with statistical significance. The analysis of the ROC curve showed a predictive positive value of 82%. Discussion: The most important risk factors were the use of surfactant and BW, the latter increasing by 23%, the risk of PDA for fewer 100 grams. Although surfactant treatment leads to improved respiratory outcomes and survival in VLBW infants, it increased the risk of PDA by an almost fourfold.